Rancang Bangun Buku Elektronik Menggunakan Mikrokontroler Dan Voice Recognition Module V3 Untuk Pencegahan Nomophobia Pada Anak Usia Prasekolah - Harist Islami; Derisma; Desta Yolanda (CHIPSET, 2022)
Nomophobia (no mobile phone phobia) is a form of phobia or fear that occurs for a person if they does not hold a mobile phone for some time then he will be stressed. This nomophobia should be prevented early on starting from the golden age of learning children 0-8 years by holding fun and interactive learning activities, because at that age the growth of the child's brain is calculated very quickly that is as much as 80%. To support their growth most of the parents, choose smartphones and gadgets of the like to support basic learning such as reading. This is because the learning offered to their child is interactive. However, it is certainly a challenge for parents to control and supervise children in using smartphones for learning activities. To solve the above, design electronic books using Microcontrollers and Voice Recognition Module V3 to support children's learning in addition to using smartphones in order to prevent nomophobia